Navigating Dining Satisfaction by Understanding Diner Hygiene Expectation and Experience - Chow, Lim Soon; Krishnapillai, Gengeswari; Lee, Chong Yee (International Review of Management and Marketing, 2019)
Indian Muslim eateries are a prominent part of Malaysian food culture and gastronomic tourism. However, according to the local the news, these eateries are plagued with negative hygienic issues. As this could endanger the diner’s overall health and well-being, it is a serious concern. Therefore, this study posits hygiene expectation and hygiene experience as the primary determinants of diner satisfaction. Expectation Disconfirmation Theory was used as a theoretical base for this study, as it allows the researcher to postulate the interaction between expectation and experience and its effect on issues concerning hygienic food service. The body of knowledge and ethical practice of Halal food literacy contributed by this study will benefit food operators that are interested in consumer dining satisfaction from a hygiene perspective. Keywords: Dining Satisfaction, Expectation, Experience, Hygiene JEL Classifications: L66, L83 DOI: https://doi.org/10.32479/irmm.7871